Physicomechanical Properties of Porous Materials by Spark Plasma Sintering. Issue 1 (2nd January 2020) - Azarniya, Abolfazl; Azarniya, Amir; Safavi, Mir Saman; Farshbaf Ahmadipour, Mohammad; Esmaeeli Seraji, Melica; Sovizi, Saeed; Saqaei, Mahboobe; Yamanoglu, Ridvan; Soltaninejad, Mohammad; Madaah Hosseini, Hamid Reza; Ramakrishna, Seeram; Kawasaki, Akira; et al.
Abstract: Metallic or ceramic micro/nanoporous materials have attracted particular attention due to some interesting structural and functional properties. There exist a variety of methods for producing porous materials by which optimized features can be reached. Spark plasma sintering (SPS) is one of these new-emerging approaches. This technique is often combined with conventional technologies and produce a variety of porous structures with tailorable microstructure and physicomechanical properties. This review addresses SPS and obtainable porous materials with nanoscale and microscale microstructural features. The processing methods, microstructural phenomena, and physicomechanical properties of these materials are discussed in some details, along with the likely future directions required for this novel field.